Pelaksanaan Kurikulum Berbasis Kompetensi (KBK) Dalam Meningkatkan Mutu Pendidikan Agama Islam - Abidin, Muhammad Zaenal; Alfatani, Ifan Ali (JoEMS (Journal of Education and Management Studies), 2023)
This research shows that PAI teachers continue to strive to improve the quality of Islamic Religious Education (PAI) through a competency-based curriculum (KBK). This implementation is carried out through various things related to teaching, which include making subject books, making modules, evaluating syllabi, implementing responsive learning, getting used to religious practices, implementing MGMPAI. Apart from that, implementation is carried out through training, workshops and seminars. This implementation is supported by the Head of Curriculum work program which is very supportive of the implementation of the KBK, as well as the Principal who cares about the needs of facilities and infrastructure. Implementation in terms of infrastructure includes creating learning workshops, providing sufficient learning media and facilities, adding library books. It turns out that this implementation is still lacking for PAI teachers at MTs Surya Buana Malang, for this reason PAI teachers at MTs Surya Buana Malang continue to work on and complete it. There are problems in implementing the Competency Based Curriculum in improving the quality of PAI teachers, including the presence of static PAI teachers and the existence of unstable teacher positions.